The hospitalization experience and state-trait anxiety among different diagnostic groups - Mizrahi, Coya. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1982., 1982)
This study investigated the state-trait anxiety levels of psychiatric inpatients in relation to the concept of hosnitalization 60 subjects; 20 neurotics, 20 psychotics and 20 substance abusers were given The State-Trait Anxiety Inventory at the time shortly after hospitalization and at the time before discharge from the hospital.The subjects were inpatients from Erenkoy Social Security Assosiation Psychiatric Hospital and were between 25 to 45 years old. The subjects had at least elementary school education. The first group of hypotheses was about the differences between neurotics and psychotics."The hypotheses stated that neuroti will have higher state and trait anxiety levels both at the time shortly after hosptalization and before discharge from the hopital. The second group of hypotheses was about the differences within subjects, that is about the change between evaluations shortly after hospitalization and before discharge from the hospital of the same subjects. The hypotheses stated that neurotics will have lower and psychotics higher state anxiety scores before discharge from the hospital while trait anxiety scores of both groups were expected to remain st8,ble. Findings about the case of substance abusers were presented altough there was no hypoothesis stated about their condition. The most general finding was that all of the three groups showed a decrease in their anxiety levels and this decrease was most significant in the neurotic group, reflected both in state and trait anxiety scores. The other important finding was that neurotic and psychotic subjects could be differentiated according to their state and trait hospital did not indicate any difference between these two groups of subjects. The results were discussed in the light of our theoretical expectations and in terms of the hospitalization experience.
Keywords: Anxiety.